Fate of pesticides in soil in a coastal lagoon area and associated water quality impacts - Tanik, A.; Gurel, M.; Zeren, O.; Gonenc, I E.; Arslan, H.; Uysal, Y.; Un, Z B.; Yalvac, M. (IWA Publishing, 2002)
Pesticides used on agricultural lands are among the significant diffuse sources of pollutants. They are poisons and can be particularly dangerous when misused and/or applied without care. Although certain characteristics of pesticides are well known, their final characteristics after they reach a waterbody are extremely difficult to estimate. Regarding the soil and water environment, it is necessary to conduct both a field study and laboratory analysis. Such a study has been performed in the catchment area of Dalyan Lagoon, Turkey, joining the Mediterranean Sea, that was selected as the pilot region. The input of pesticides, transport in soil and transfer to the water environment together with their probable impacts on water quality are determined by conducting detailed field surveys and water residue analyses. Within the scope of the study, the behavior and fate of pesticides both in soil and water are investigated in detail. Water residue experiments are conducted on four sets of water samples representing the seasons of the year 1999-2000 for the pre-selected 6 pesticides. Two sets of water samples (surface and bottom) are taken from the 16 stations along the lagoon channel and two lakes within the catchment area. The results and findings show the significance of the use of pesticides as they exist in the water environment around and/or slightly above the limits stated in the national current regulations except dichlorvos which presents very high values compared to its tolerance limit. Of particular interest, the results are used to enlighten the farmers and the public and increase awareness of pesticides as contaminants in valuable coastal waters.
Keywords: Turkey; Agriculture; Public Policy; Risk Assessment; Reference Values; Water Movements; Soil Pollutants; Pesticides; Water Pollutants, Chemical; Environmental Monitoring